Multilingualism as a catalyst for Open Science - Havemann, Johanna (My University, 2024)
This presentation was held during the CATALASI Webinar on Mainstreaming of Open Science and Digitization of Research on February 8, 2024. CATALISI | Catalysation of institutional transformations of Higher Education Institutions through the adoption of acceleration services. Funded by the European Union under Grant Agreement n. 101094917. | https://catalisi.eu
Keywords: Multilingualism; Open Science; Communication